Stranger than fiction. Falsità e finzione nell’epoca della realtà aumentata - Montebugnoli, Anna (Elephant & Castle, 2017)
This essay analyses the aesthetics issues of augmented reality in the complex distinction of falseness and fiction implied in any act of producing or reproducing of images and artefacts. The boundary between the two concepts lies on the different intention that leads their peculiar way of dealing with reality. Falseness implies indeed an ontological (and axiological) confusion to the degree that its products try to substitute reality by imitating it. On the other hand, fiction doesn’t try to deceive: its artefacts simply belong to an inferior degree of ontology. Using as a case-study the Pokemon GO phenomenon and the moral debate that followed it, this article aims to outline a genealogy of the controversy surrounding the mimetic and poietic products as they blur the line between truth and falseness, reality and fiction.